Community-based insights on maternal nutrition knowledge and its role in preventing stunting and wasting in rural Indonesian children - Wulandari, Dewi Triloka; Azizah, Ninik; Rahmawati, Vivin Eka; Annuchasari, Helmi (Journal of Current Health Sciences, 2025)
Stunting and wasting remain significant public health challenges in Indonesia, with the 2023 SSGI survey reporting prevalences of 21.6% and 7.7% respectively—figures that exceed global targets, especially in rural areas. This qualitative case study, conducted in Mojowarno, Jombang Regency, was chosen due to its persistently high rates of child undernutrition and limited access to nutrition education. The study aimed to explore the relationship between maternal nutrition knowledge and the incidence of stunting and wasting among toddlers. Data were collected from 24 informants, including mothers, health workers, and a community volunteer, through in-depth interviews and triangulated with document and observation data. Results revealed that low maternal nutrition knowledge—characterized by limited understanding of balanced meals, meal timing, and child feeding practices—was a primary driver of malnutrition, regardless of parental occupation or income. The study highlights the urgent need for sustainable, community-based nutrition education interventions and cross-sectoral collaboration. Findings inform local policy and support targeted strategies for reducing stunting and wasting in similar rural contexts. Abstrak: Stunting dan wasting tetap menjadi tantangan kesehatan masyarakat yang signifikan di Indonesia, di mana Survei Status Gizi Indonesia (SSGI) 2023 melaporkan prevalensi masing-masing sebesar 21,6% dan 7,7%—angka yang masih melebihi target global, terutama di wilayah pedesaan. Studi kasus kualitatif ini dilakukan di Mojowarno, Kabupaten Jombang, yang dipilih karena tingginya angka kekurangan gizi pada anak dan terbatasnya akses edukasi gizi di wilayah tersebut. Penelitian ini bertujuan untuk mengkaji hubungan antara pengetahuan gizi ibu dengan kejadian stunting dan wasting pada balita. Data dikumpulkan dari 24 informan yang terdiri dari ibu balita, tenaga kesehatan, dan kader masyarakat melalui wawancara mendalam, serta triangulasi dengan data dokumen dan observasi. Hasil penelitian menunjukkan bahwa rendahnya pengetahuan gizi ibu—yang tercermin pada pemahaman terbatas tentang pola makan seimbang, jadwal makan, dan praktik pemberian makan anak—menjadi faktor utama terjadinya malnutrisi, terlepas dari pekerjaan atau pendapatan orang tua. Studi ini menyoroti perlunya intervensi edukasi gizi berbasis komunitas yang berkelanjutan serta kolaborasi lintas sektor. Temuan ini dapat menjadi acuan kebijakan lokal dan mendukung strategi terarah untuk menurunkan angka stunting dan wasting di wilayah pedesaan serupa.